The Effect Of Service Quality And Facilities On Outpatient Patient Satisfaction At Merapi 1 Public Health Center, Lahat Regency - Lini Fisti; Tri Rusilawati; Amaludin Amaludin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to find out how the influence of service quality and facilities affects partially and simultaneously on outpatient satisfaction at the Merapi 1 Health Center, Lahat Regency. The sample in this study was 97 respondents. The sample extraction method used by the researcher is incidental sampling. This type of research is a quantitative research using multiple linear regression analysis techniques which is processed using the SPSS application and produces regression equations. Y-9.615 +0.633 X1 +0.141 X2 + The results in this study are: there is a significant influence between service quality on outpatient satisfaction at Merapi 1 Health Center Lahat Regency, there is a significant influence between facilities on outpatient satisfaction at Merapi 1 Health Center Lahat Regency. The F test showed that the quality of services and facilities had a simultaneous effect on outpatient satisfaction at the Merapi 1 Health Center, Lahat Regency.